Singular adaptations in the carbon assimilation mechanism of the polyextremophile cyanobacterium Chroococcidiopsis thermalis - Aguiló-Nicolau, Pere; Galmés, Jeroni; Fais, Giacomo; Capó-Bauçà, Sebastià; Cao, Giacomo; Íñiguez Moreno, Concepción (Springer, 2023)
Cyanobacteria largely contribute to the biogeochemical carbon cycle fixing ~ 25% of the inorganic carbon on Earth. However, the carbon acquisition and assimilation mechanisms in Cyanobacteria are still underexplored regardless of being of great importance for shedding light on the origins of autotropism on Earth and providing new bioengineering tools for crop yield improvement. Here, we fully characterized these mechanisms from the polyextremophile cyanobacterium Chroococcidiopsis thermalis KOMAREK 1964/111 in comparison with the model cyanobacterial strain, Synechococcus sp. PCC6301. In particular, we analyzed the Rubisco kinetics along with the in vivo photosynthetic CO2 assimilation in response to external dissolved inorganic carbon, the effect of CO2 concentrating mechanism (CCM) inhibitors on net photosynthesis and the anatomical particularities of their carboxysomes when grown under either ambient air (0.04% CO2) or 2.5% CO2-enriched air. Our results show that Rubisco from C. thermalis possess the highest specificity factor and carboxylation efficiency ever reported for Cyanobacteria, which were accompanied by a highly effective CCM, concentrating CO2 around Rubisco more than 140-times the external CO2 levels, when grown under ambient CO2 conditions. Our findings provide new insights into the Rubisco kinetics of Cyanobacteria, suggesting that improved Sc/o values can still be compatible with a fast-catalyzing enzyme. The combination of Rubisco kinetics and CCM effectiveness in C. thermalis relative to other cyanobacterial species might indicate that the co-evolution between Rubisco and CCMs in Cyanobacteria is not as constrained as in other phylogenetic groups.
Keywords: Enzimas - Cinética; Cianobacterias - Biotecnología; Carbono - Fijación; Cyanobacteria; Rubisco; CO2 concentrating mechanisms; CO2 fixation; Photosynthesis